Churg-Strauss vasculitis in patient who received montelukast - Ćupurdija, Vojislav; Čekerevac, Ivan; Petrović, Marina; Kostić, Gordana; Suša, Romana; Lazić, Zorica (Vojnosanitetski pregled, 2020)
AbstractIntroduction. Montelukast is a selective leukotriene receptor antagonist. One of side effects of this drug class is the Churg- Strauss syndrome (CSS). There is still no reliable evidence whether the expression of this syndrome could be masked by high doses of corticosteroids and become expressed by termination of corticosteroid use, or whether it could be a consequence of leukotriene receptor antagonists use. Case report. Female patient, aged 49 years, was hospitalized with symptoms of fever, dyspnea, cough and increased sputum production with occasional hemoptysis. She was treated for asthma during the previous year. Leukocyte differential formula registered 44% of eosinophils. IgE value was extremely elevated, with value measured to 580 kU/L and eosinophile cation protein value was 15.1 µg/L. Computed tomography of the chest described changes in the form of ground glass located in all lobes of the right lung and in the upper lobe of the left lung. Computed tomography of paranasal sinuses described changes that could resemble to polyposis, chronic sinusitis, and possible granulomatosis. Mononeuritis of peroneal nerve of the right leg was proven by electromyographic examination. Bone marrow biopsy indicated hypercellularity with domination of eosinophilic granulocytes (30%). Five out of six criteria were noted in patient’s clinical presentation, after which the diagnosis of CSS was set. The patient began treatment with high doses of corticosteroids while montelukast was discontinued which resulted in disease remission. Conclusion. Although there is no evidence that leukotriene modifiers cause the CSS in all patients with asthma, in case of frequent exacerbations with the appearance of pulmonary infiltrates, eosinophilia and paranasal sinus abnormalities make one think of this form of vasculitis.
Keywords: churg-strauss syndrome; leukotriene antagonists; diagnosis; drug therapy; treatment outcome; asthma.